A Role Delineation Study of Hand Surgery in the USA: Assessing Variations in Fellowship Training and Clinical Practice. (March 2014) - Aliu, Oluseyi; Chung, Kevin C.
Background: We examined the fellowship experience of hand surgeons in the USA to identify gaps and variations in exposure to essential skills and knowledge during hand fellowship. Methods: We conducted a web-based survey of the entire American Society for Surgery of the Hand and American Association for Hand Surgery membership. We inquired about the level of exposure received to 170 knowledge topics and procedures during fellowship. We used factor analysis to group the knowledge topics and procedures into 79 scales of related items and calculated mean exposure ratings for each scale. We compared the ratings between graduates of plastic surgery (PS) and orthopedic surgery (OS) Residency Review Committee (RRC)-accredited fellowships. Results: Our response rate was 21 % ( n =562). Plastic surgery RRC-accredited fellowship graduates reported inadequate exposure for proficiency in 22 % (17/79) of the knowledge topic and procedure scales whereas graduates of OS RRC-accredited fellowships reported inadequate exposure for proficiency in 10 % (8/79) of the scales. Moreover, 11 and 21 % of graduates from PS RRC-accredited fellowships reported receiving no exposure in distal radius/ulna and forearm conditions, respectively, whereas only 1 and 2 % of graduates from OS RRC-accredited fellowships reported receiving no exposure in the same domains, respectively. Conclusions: Hand surgeons reported significant variations in exposure to essential skills and knowledge. Additionally, in a considerable number of knowledge topics and procedures, a majority of participants in both groups reported what they perceived as inadequate or no exposure during their hand surgery fellowship.